KOMPETENSI KEPRIBADIAN TUTOR DALAM PEMBELAJARAN MATEMATIKA PAKET C DI PKBM HARAPAN BANGSA, KECAMATAN TAMBANG, KABUPATEN KAMPAR - Putri, Wiwin Rahayu; Achmad, Said Suhil; Maemunaty, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study examines the tutor's personal competence in learning mathematics Package C at PKBM Harapan Bangsa, Kecamatan Tambang , Kabupaten Kampar. This study uses a descriptive qualitative paradigm approach. Research subjects will be determined based on purposive sampling, informants in this study are 3 (three) people. Data collection is done by observation (observation), documentation, in-depth interviews (indept interview), data analysis is done by; data reduction; data exposure (data display); and conclusion drawing and verification (conclusion drawing / verifying). The results showed: 1) Tutor mathematics subjects in Package C implement aspects of personality competencies, from indicators tutors have stable and stable personalities, tutors have mature personalities, tutors have wise personalities, tutors have authoritative personalities, tutors have moral personality.Keywords: Personality Competence, Tutor